2017
DOI: 10.1637/11718-072317-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Chronologic Analysis of Gross and Histologic Lesions Induced by Field Strains of FAdV-1, FAdV-8b, and FAdV-11 in Six-Week-Old Chickens

Abstract: Inclusion body hepatitis (IBH) is a disease affecting broiler chicken flocks worldwide. Several serotypes of fowl adenovirus (FAdV) have been implicated in disease outbreaks, with and without immunosuppression as a predisposing factor. IBH usually occurs in flocks up to 30 days of age; it is seldom seen in older birds. The objective of this study was to determine whether the pathogenicity for older birds of three FAdV field strains, belonging to serotypes 1, 8b, and 11, in the absence of immunosuppressive fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Indeed, the presence of INIB in hepatocytes have been shown by inoculation of FAdV to specific pathogen free (SPF) embryonated eggs via the chorioallantoic membrane and was observed at 5–6 dpi and the adenovirus particles were identified in liver samples of embryos by transmission electron microscopy [36]. Furthermore, SPF chickens infected with different strains of FAdV showed the presence of INIB in hepatocytes at the histological examination of liver tissues [32, 37, 38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the presence of INIB in hepatocytes have been shown by inoculation of FAdV to specific pathogen free (SPF) embryonated eggs via the chorioallantoic membrane and was observed at 5–6 dpi and the adenovirus particles were identified in liver samples of embryos by transmission electron microscopy [36]. Furthermore, SPF chickens infected with different strains of FAdV showed the presence of INIB in hepatocytes at the histological examination of liver tissues [32, 37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…The nucleotide sequences analysis showed that the three FAdV isolates belonged to FAdV serotype 11 of the D genotype group. This strain was responsible for different inclusion body hepatitis outbreaks in poultry in Canada [28], China [59], Hungary [29], Australia [38], Lebanon [31], Spain [32] and Iran [60].…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies (Yates et al, 1977;Mockett & Cook, 1983) a three-week period was considered optimal for the development of protecting antibodies. Other factors taken into consideration included a suitable age and size of birds to safely administer the IM vaccination, as well as an appropriate age to challenge the birds following the three week period for development of immunity, which was identified as 6 weeks of age in a previous study (Steer-Cope et al, 2017).…”
Section: Vaccinationmentioning
confidence: 99%
“…Inoculation was performed via intraperitoneal (IP) injection with 0.5 mL of inoculum containing 10 6 TCID 50 of the virus. The dose was deemed to be suitable for inducing a strong challenge response without resulting in sudden mortality, due to the lower susceptibility to infection of older birds observed in a previous study (Steer-Cope et al, 2017). The birds in the fourth group were inoculated with sterile phosphate-buffered saline (PBS) and used as negative controls.…”
Section: Challengementioning
confidence: 99%
See 1 more Smart Citation